The impact of the COVID-19 pandemic on the prevalence and risk factors of workplace violence among healthcare workers in China - Qi, Miao; Hu, Xiuli; Liu, Jun; Wen, Jing; Hu, Xue; Wang, Zhizhong; Shi, Xiuquan (Frontiers in Public Health, 2022)
Background: The pandemic of COVID-19 has significantly increased the burden on healthcare workers and potentially affect their risk of workplace violence (WPV). This study aimed to explore the prevalence and risk factors of WPV among healthcare workers during the peaking and the remission of the COVID-19 pandemic in China. Methods:Using the snowball method, a repeated online questionnaire survey was conducted among Chinese healthcare workers from March 27th to April 26th in 2020 and 2021, respectively. Data included healthcare workers' socio-demographic and occupational characteristics, psychological status, and workplace violence. Results: A total of 3006 samples in 2020 and 3465 samples in 2021 were analyzed. In 2020, the prevalence of WPV and witnessing colleagues suffering from WPV among healthcare workers were 64.2% and 79.7% respectively. Compared with 2020, the prevalence decreased by 11.0% and 14.4% in 2021, respectively. Logistic regression showed that WPV in 2020 was influenced by males, long working experience, working in the psychiatric department, direct contact with COVID-19 patients, self-discovery of medical errors, moral injury, depression, and anxiety (minimum OR=1.22, maximum OR=2.82). While risk factors of WPV in 2021 included males, working in psychiatric departments, self-discovery of medical errors, moral injury, depression, and anxiety (minimum OR=1.33, maximum OR=3.32); and protective factors were holding a master's degree (OR=0.78) and working in other departments (OR=0.54). Conclusion:This study retains the common effects of WPV among healthcare workers, though after the baptism of the COVID-19 pandemic, the prevalence of WPV among healthcare workers decreased; however, part of the influencing factors changed. In addition, COVID-19 has seriously affected the mental health of healthcare workers, and the effect of mental health problems on WPV should also attract more attention.